Co-digestão anaeróbia de resíduos vegetais e águas residuárias de suinocultura em reatores horizontais de leito fixo e alta taxa - Mazareli, Raissa Cristina da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Four horizontal fixed bed and high rate reactors were used to evaluate the removal of organic matter, coliforms and nutrients and also the production of methane in anaerobic co-digestion process using as a substrate different concentrations of vegetable waste (tomato and banana) and swine wastewater. Physical and chemical analyzes were performed in the influent and effluent in order to verify system stability. The results showed buffering efficiency in the process, maintaining the pH near 7,0. The first reactor (R1) occurred the maximum volumetric production of methane with average values of 1,08 L CH4 (Ld-1) with OLR of 11 g DQO (Ld)-1. The biggest specific production of methane occurred at the beginning of the test 4 with 0,25 L CH4 g total COD removed in the R1, equivalent to 88% of total COD removed was converted to methane. The specific production of methane g dissolved COD was higher with application of OLR of 5,5 g COD (Ld) -1 the first reactor. The CH4 decreased when there was vegetable waste increase in inffluent. The system (R1+R2+R3+R4) improved the quality of the inffluent with removal of 99,99% of total and fecal coliforms as well as maximum removal of 95% of total COD, 86% of dissolved COD, 97% of TSS and 98% of VSS. The system also occurred accentuated removal of macro and micronutrients (86, 75, 95, 99, 96, 63 and 83% of total P, Mg, Zn, Cu, Mn, Fe and total nitrogen respectively), and sludge production with relationship SV/ST for agricultural use. Reactors profile analysis demonstrated removal of the organic matter and production of biogas would need only three reactors ...

Quatro reatores anaeróbios horizontais de leito fixo e alta taxa instalados em série, com alimentação contínua foram utilizados para avaliar a remoção de matéria orgânica, coliformes e nutrientes e também a produção de metano no processo de co-digestão anaeróbia utilizando como substrato diferentes concentrações de resíduo vegetal (tomate e banana) e águas residuárias de suinocultura. Análises físico-químicas foram realizadas nos afluentes e efluentes, afim de verificar a estabilidade do sistema. Os resultados demonstraram eficiência de tamponamento no processo, mantendo pH próximo a 7,0. No primeiro reator (R1) ocorreu a maior produção volumétrica de metano com valor médio de 1,08 L CH4 (L d-1) com COV de 11 g DQO (Ld)-1. A maior produção específica de metano ocorreu no R1 no começo do ensaio 4 com valor de 0,25 L CH4 g DQOtotal removida, equivalente a 88% da DQOtotal removida foi convertida em metano. Já a produção específica de metano por g DQOdiss foi maior com aplicação da COV de 5,5 g DQO (Ld)-1 no primeiro reator. A porcentagem de CH4 no biogás diminuiu quando houve acréscimo de resíduo vegetal no afluente. O sistema (R1+R2+R3+R4) melhorou a qualidade do afluente com remoções de 99,99% de coliformes totais e termotolerantes, assim como remoções máximas de 95% de DQOtotal, 86% de DQO dissolvida, 97% de SST e 98% de SSV. No sistema também ocorreram remoções acentuadas de macro e micronutrientes (86, 75, 95, 99, 96, 63 e 83% de P-total, Mg, Zn, Cu, Mn, N total e Fe respectivamente), além da produção de lodo com relação SV/ST para fins de utilização agrícola. Análise do perfil dos reatores demonstrou que para remoção de matéria orgânica e produção de biogás seria necessário somente três reatores, mas para...
Keywords: Metano; Residuos organicos; Biogas; Fermentação; Matéria orgânica; Methane